Endocrine Therapy of Estrogen Receptor-Positive Breast Cancer Cells: Early Differential Effects on Stem Cell Markers - Leung, Euphemia Y.; Askarian-Amiri, Marjan E.; Sarkar, Debina; Ferraro-Peyret, Carole; Joseph, Wayne R.; Finlay, Graeme J.; Baguley, Bruce C. (Frontiers in Oncology, 2017)
Introduction: Endocrine therapy of breast cancer, which either deprives cancer tissue of estrogen or prevents estrogen pathway signaling, is the most common treatment after surgery and radiotherapy. We have previously shown for the estrogen-responsive MCF-7 cell line that exposure to tamoxifen, or deprivation of estrogen, leads initially to inhibition of cell proliferation, followed after several months by the emergence of resistant sub-lines that are phenotypically different from the parental line. We examined the early responses of MCF-7 cells following either exposure to 4-hydroxytamoxifen or deprivation of estrogen for periods of 2 days to 4 weeks. Methods: Endocrine-sensitive or -resistant breast cancer cell lines were used to examine the expression of the stem cell gene SOX2, and the Wnt effector genes AXIN2 and DKK1 using quantitative PCR analysis. Breast cancer cell lines were used to assess the anti-proliferative effects (as determined by IC50 values) of Wnt pathway inhibitors LGK974 and IWP-2. Results: Hormone therapy led to time-dependent increases of up to 10-fold in SOX2 expression, up to 3-fold in expression of the Wnt target genes AXIN2 and DKK1, and variable changes in NANOG and OCT4 expression. The cells also showed increased mammosphere formation and increased CD24 surface protein expression. Some but not all hormone-resistant MCF-7 sub-lines, emerging after long-term hormonal stress, showed up to 50-fold increases in SOX2 expression and smaller increases in AXIN2 and DKK1 expression. However, the increase in Wnt target gene expression was not accompanied by an increase in sensitivity to Wnt pathway inhibitors LGK974 and IWP-2. A general trend of lower IC50 values was observed in 3-dimensional spheroid culture conditions (which allowed enrichment of cells with cancer stem cell phenotype) relative to monolayer cultures. The endocrine resistant cell lines showed no significant increase in sensitivity to Wnt inhibitors. Conclusion: Hormone treatment of cultured MCF-7 cells leads within two days to increased expression of components of the SOX2 and Wnt pathways and to increased potential for mammosphere formation. We suggest that these responses are indicative of early adaptation to endocrine stress with features of stem cell character, and that this facilitates the survival of emerging hormone-resistant cell population.